2014
DOI: 10.1371/journal.pone.0085592
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of PTPN12 Correlates with Tumor Recurrence and Poor Survival of Patients with Hepatocellular Carcinoma

Abstract: BackgroundProtein tyrosine phosphatase non-receptor type 12 (PTPN12), has been identified as a potent tumor suppressor in human cancers and a critical regulator of cell adhesion and migration. However, the PTPN12 expression and its prognostic significance in HCC have not been well elucidated.Methodology/Principal FindingsIn this study, tissue microarray-based immunohistochemistry (IHC) was investigated in an HCC cohort with adjacent liver tissues as controls. The resulting data were analyzed using receiver ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…In this study, we propose that PTPN12 plays a key role in CD99-mediated negative regulation of ␤1 integrin activity and tumor progression. This assumption is consistent with recent reports showing that PTPN12 functions as a tumor suppressor (67)(68)(69). Taken together, our results suggest that CD99-derived agonist ligands have potential as novel therapeutic reagents to suppress tumor progression via negative regulation of ␤1 integrin activity.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we propose that PTPN12 plays a key role in CD99-mediated negative regulation of ␤1 integrin activity and tumor progression. This assumption is consistent with recent reports showing that PTPN12 functions as a tumor suppressor (67)(68)(69). Taken together, our results suggest that CD99-derived agonist ligands have potential as novel therapeutic reagents to suppress tumor progression via negative regulation of ␤1 integrin activity.…”
Section: Discussionsupporting
confidence: 93%
“…This alteration was more common in TNBC. Likewise, decreased expression of PTPN12 was reported in other human malignancies, including non-small-cell lung carcinoma, esophageal squamous cell carcinoma, nasopharyngeal carcinoma, and hepatocellular carcinoma (18)(19)(20)(21). In all cases, loss of PTPN12 correlated with aggressiveness and poor prognosis.…”
mentioning
confidence: 63%
“…This could also be the case for other types of human cancer in which loss of PTPN12 is more often seen in aggressive subtypes. These include lung cancer, nasopharyngeal cancer, esophageal cancer, and hepatocellular carcinoma (14,18,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that knockdown of PTPN12 significantly increased the migration capacity and expression of mesenchymal markers and EMT-TFs in multiple human HCC cell lines, indicating that PTPN12 is a universal EMT suppressor in cancer cells as well as in normal tissues. Decreased expression of PTPN12 is also negatively correlated with tumor recurrence and survival of HCC patients (56), further supporting the importance of this tumor suppressor in HCC. Interestingly, Ptpn12-deficient mouse embryos exhibited a failure of liver development, leading to lethality (57), suggesting that Ptpn12 may play a fundamental role in liver development as well.…”
Section: Discussionmentioning
confidence: 83%